Middle Palaeolithic flint procurement in Central Mediterranean Iberia: Implications for human mobility - Aleix Eixea; Clodoaldo Roldán; Valentín Villaverde; João Zilhão (Journal of Lithic Studies, 2014)
Different flint types from the Middle Palaeolithic site of Abrigo de la Quebrada (Chelva, Valencia) are characterized,  both macro- and microscopically, and compared with types found at other localities in the region. Although procurement predominantly concerned the immediate vicinity of sites, our results show the presence of the same types in assemblages separated by distances of up to 120 km. The long distances involved are suggestive of a pattern of North-South mobility of human groups along the coastline of central Mediterranean Iberia.